Pedagogy of Care Equipped International Post-Secondary Students to Thrive in Times of Post-Pandemic Crisis - Amtul, Zareen; Yuan, Xuechen (Journal of Teaching and Learning, 2026)
According to several national indices and post‑pandemic surveys, post‑secondary international students remain at high risk for chronic stress and declining mental health. We therefore proposed a multidisciplinary study to examine the impact of a remote, modular intervention program across three wellness domains: 1) Social, 2) Emotional, and 3) Professional Learning (SEPL). These domains were selected to identify areas in which students might benefit most from targeted support. The SEPL modules were designed to help students: Social (S): learn how to network differently through virtual coffee chats to strengthen socio‑emotional connectedness; Emotional (E): openly share fears and anxieties related to educational uncertainty, work‑related stress, and experiences of discrimination; and Professional Learning (P): invest in personal and professional development, continue job searching, and engage in academic or extracurricular activities to build resilience and support ongoing learning. Survey responses indicated improvements in students’ post‑pandemic distress across these wellness domains, as well as enhanced academic achievement in the associated course following the SEPL intervention. Integrating SEPL‑based pedagogical practices into our curriculum would allow us to provide structured support for stress management, emotion regulation, resilience, and work‑life balance. This approach would help students regain a sense of control amid pandemic‑related challenges, while also offering instructors a framework to strengthen their teaching practices.